2012
DOI: 10.21608/jappmu.2012.82943
|View full text |Cite
|
Sign up to set email alerts
|

Stocking Density Effects on Performance and Physiological Changes of Laying Japanese Quail

Abstract: The current study was conducted to examine the effects of different cage stocking densities and sex on performance and physiological changes of laying Japanese quail reared under hot climate region for a period of 11 weeks (10 to 21 weeks of age). A total number of 600 Japanese quails (400 females and 200 males) at 10 weeks old were randomly distributed in a randomized block design with 4 treatments (71, 59, 50 and 43 quail per cage) or (140, 170, 200 and 233 cm 2 / bird) respectively. Each treatment group was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…Hen-Day Production decreased correspondingly with an increase in stocking density and was better in Group I and II when compared with Groups III and IV. Hen-Housed production followed a similar trend as observed in hen-day production while egg production per hen decreased significantly (p < 0.05) as stocking density increased which agrees with other authors' observations in quail farming experiments (Nagarajan et al, 1991;Sohail et al, 2001;Özbey et al, 2004;El-Shafei et al, 2012).…”
Section: Resultssupporting
confidence: 90%
“…Hen-Day Production decreased correspondingly with an increase in stocking density and was better in Group I and II when compared with Groups III and IV. Hen-Housed production followed a similar trend as observed in hen-day production while egg production per hen decreased significantly (p < 0.05) as stocking density increased which agrees with other authors' observations in quail farming experiments (Nagarajan et al, 1991;Sohail et al, 2001;Özbey et al, 2004;El-Shafei et al, 2012).…”
Section: Resultssupporting
confidence: 90%
“…Our results agree with the previous researches (Daniela et al, 2018;EL-Sheikh et al, 2016;El-Shafei et al, 2012) who indicated that feed consumption for Japanese quail significantly decreased with increasing cage density. Likewise, the effect of YE on feed consumption agree with Liu et al (2002) who found reduction feed consumption in quails at 0.2 % yeast.…”
Section: Feed Intake and Feed Conversion Ratiosupporting
confidence: 93%
“…The effect of stocking density on FCR values in the present study are in agreement with those of EL-Sheikh et al (2016) who reported that FCR values were significantly poorer with increasing the number of quails/square meter throughout the production period. On the other hand, Santos et al (2011);EL-Shafei et al (2012) observed FCR/kg of egg produced was better (P<0.05) for quail layers raised under higher floor space. Moreover, Faitarone et al (2005) stated that, FCR values of quails were not significantly affected among treatment when stocked at 246, 211, 176 and 151 cm 2 /quail.…”
Section: Feed Intake and Feed Conversion Ratiomentioning
confidence: 93%
“…Several studies have addressed the SD's effect on performance in laying hens, although few studies have focused on laying quails, and the results are variable [2,16,18]. Moreover, there is a scarcity of information on the effects of SD and AA supplementation by emphasizing the nutrient digestibility, performance, and egg quality of quails raised in high-temperature environments.…”
Section: Introductionmentioning
confidence: 99%
“…AA is also required for mineral and amino acid metabolism, as well as the production of white blood cells required for birds' immune status [9]. The positive effects of AA supplementation have been documented in breeder or laying hens [12,14,15] and quails [16,17], although those effects indicated variable results.…”
mentioning
confidence: 99%